[M(Me6Tren)X]X complex as efficacious bifunctional catalyst for CO2 cycloaddition: The synergism of the metal and halogen ions. (July 2022) - Wei, Fen; Tang, Jia; Zuhra, Zareen; Wang, Shoushan; Wang, Xiaoxia; Wang, Xiufang; Xie, Guanqun
Abstract: Efficient catalysis for fixation and conversion of CO2 is of significance to carbon neutralization. Here, a series of C 3 symmetric bifunctional complex catalysts with different metals (Ni, Co, Cu) have been strategically synthesized and evaluated in the CO2 cycloaddition with epoxides. Among these catalysts, [Ni(Me6 Tren)I]I 3c exhibits the best performance affording up to 99.1% yield of chloropropylene carbonate under ambient (60 °C, CO2 balloon), cocatalyst- and solvent-free conditions. TPD and XPS showed 3c possessed excellent acid center. Single crystal X-ray diffraction indicated the facile dissociation of Ni-I based on the bond length information. The synergistic effect of the Ni(II) acidic center, the axial and outer iodine ions was discussed. Based on the structure-activity relationship, plausible reaction pathways were proposed for the bifunctional catalysts. Moreover, a large-scale synthesis of chloropropylene carbonate (350 mmol) and recyclability of 3c catalyst highlight its potential for industrial applications. Graphical Abstract: ga1 Highlights: A series of C3 symmetric bifunctional catalysts (Ni, Co, Cu) have been synthesized. Their activities have been evaluated to explore their structure-activity relationship for CO2 cycloaddition reaction. [Ni(Me6Tren)I]I showed excellent catalytic activity under ambient, cocatalyst- and solvent-free conditions. The synergism of the Ni(II) acid center and the two I ions were rationalized.